Investigate the velocity difference between MRI measurement and CFD simulation on patient-specific blood flow analysis - Hong, Lim Seh; Mohd Azrul Hisham, Mohd Adib; Mohd Shafie, Abdullah; Nur Hartini, Mohd Taib; Radhiana, Hassan; Azian, Abd Aziz (Springer Science and Business Media Deutschland GmbH, 2022)
This paper tends to investigate the velocity difference between magnetic resonance imaging (MRI) measurement and computational fluid dynamics (CFD) simulation on patient-specific blood flow analysis. Three patients diagnosed with particular cerebral aneurysms are involved in the current investigation. The raw image data from patients have been processed through image segmentation for model reconstruction using several threshold coefficients,